A Retrospective Cross Sectional Study of the Effectiveness of a Project in Improving Infant Health in Bwindi, South Western Uganda - Kamugisha, S. Robert; Dobson, Andrew E.; Stewart, Alex G.; Haven, Nahabwe; Mutahunga, Birungi; Wilkinson, Ewan (Frontiers in Public Health, 2018)
Introduction Implementation of low-cost community-based interventions to improve infant health have been shown to be feasible and beneficial as a means of progressing towards the Sustainable Development Goals. Bwindi Community Hospital, Uganda implemented a 3-year nurse-led community project to address child-health issues. Nurses supported Community Health Volunteers (CHVs) and visited mothers pre- and/or postnatally to assess and educate the mother and child. CHV’s gathered data and gave basic advice on health and hygiene to mothers. The hypothesis was that increased contact with the households and interventions by nurses and CHV’s, would have a measurable association with improving health and reducing the infant mortality. Methods This was a retrospective cohort study using routine data of all children born between January 2015 and December 2016. There were three interventions: antenatal nurse visit, postnatal nurse visit and CHV participation. Children received different numbers of the interventions. Outcomes measured were: facility-based delivery, immunization completeness, nutritional status and infant mortality. Odds ratios, adjusted odds ratios and multivariate logistic regression were used to assess associations between interventions and outcomes. Results Of the 4442 children born, 81% were visited by a nurse antenatally, and 10% postnatally and 7% were in households with a high participating CHV. Households receiving a postnatal visit were more likely to complete immunization (aOR:1.55, p=0.016) and have the infant survive (aOR: 1.90, p=0.05). Those living in a hard-to-reach village (no road access) were less likely to have a delivery in a health facility (aOR:0.55, p<0.001) and for a child to die (aOR:0.69, p=0.03). Having been exposed to two or more interventions was associated with a child having all positive outcomes (aOR 0.78,p=0.03). Conclusion Visits to mothers after birth, by a nurse to educate and to identify child illness, to mothers after birth had a significant association with reducing infant mortality and improved health as measured by completion of immunizations. Community health interventions could potentially have a greater impact if focused on hard-to-reach areas. Lack of integrated assessment data limited the evaluation possible. Building evaluation into all project designs, whether local or internationally funded, would enable greater learning and hence better use of resources.